Recruitment Dynamics and Organizational Performance of Selected Banks in Delta State - Akpenyi Florence Dumbiri; Kifordu Anyibuofu Anthony; Odita O. Anthony (Review of Ethics in Sustainable Finance and Accounting, 2025)
While the business world is starting to understand the significance of recruitment dynamics, there is still a lack of scholarly research investigating the reasons behind how recruitment dynamics affect organizational performance, especially in the banking industry. The aim of this research was to fill a gap in knowledge by performing a descriptive analysis with primary data gathered from 176 employees at specific banks in Delta State, Nigeria, using a straightforward random sampling technique. The information was obtained through questionnaires filled out by the employees themselves and then examined using descriptive statistics, bivariate correlation analysis, and multiple linear regression analysis. The results showed a strong positive linear relationship between Culture and performance, and the regression analysis revealed that the dimensions of recruitment dynamics (work experience, educational background, and cultural outfit) are statistically significant predictors of organizational performance at a 95% level of confidence. Specifically, the findings indicate that a unit increase in work experience, education, and Culture leads to a significant increase in organizational performance. The study concludes that recruitment dynamics have a significant impact on organizational performance in the banking sector and recommends that banks leverage social media platforms and short text messaging services to facilitate prompt reporting and action on misconduct and corrupt practices.